Substance use among young people in the West Arsi Zone, Ethiopia: A cross-sectional study - Jemal Ebrahim Shifa; Jon Adams; Daniel Demant (PLoS ONE, 2025)
Introduction Substance use is a pressing public health concern in young Ethiopians, impacting their physical, psychosocial, and emotional well-being and productivity. However, there is a limited understanding of the prevalence and factors associated with substance use in this population both across Ethiopia and in the West Arsi zone specifically. This study investigates the prevalence of substance use and associated factors among young people in the West Arsi Zone, Ethiopia. Methods A community-based cross-sectional survey was conducted among 427 randomly selected young people aged 14–29 in the West Arsi zone of the Oromia region, Ethiopia. Data were collected using structured interviewer-administered questionnaires. Logistic regression analysis was performed to determine the association between the outcome and independent variables. Ethical approval was obtained from the University of Technology Sydney, Australia, and Madda Walabu University, Ethiopia. Results A total of 424 participants were included in the analysis, giving a response rate of 99.3%. The overall lifetime prevalence of any substance use among the study participants was 48.1% (95% CI: 43.3%, 53.0%) and the prevalence of current substance use was 72.5% (95% CI: 65.9, 78.5). Among lifetime users, 76.5% reported chewing khat, 49.0% drinking alcohol, 33.3% using various forms of tobacco, and 23.0% using cannabis. Being male, having a single marital status, a family history of substance use, low perceived social support, and the presence of mental health conditions were associated with an increased likelihood of substance use. Conclusions About half of the study participants reported a history of use of at least one substance from alcohol, khat, tobacco, or cannabis in their lifetime, highlighting the need for appropriate focused interventions to help address the growing challenges of substance use amongst young people in Ethiopia.